Measuring the Amount of Apically Extruded Debris of Endosequence ESR, R-Motion, F6 SkyTaper and Endosequence CM Files in Curved Canals: An in Vitro Study (Mustansiria Dental Journal, 2023)
Aim of the study: Assessing the relationship between Endosequence ESR, R-motion, F6 sky taper and Endosequence CM files use in curved canals and the quantity of apically extruded debris.Materials and methods: 60 curved mesial roots of lower molars with 20-30 degree curvature were selected for this study, The samples were then divided randomly into four groups (n = 15)-Group I: EndoSequence ESR, Group II: R-motion (RM), Group III: F6 SkyTaper and Group IV: EndoSequence CM. This research followed the protocol devised by Myers and Montgomery, wherein debris were collected in vials and weighed before and after instrumentation using a 0.00001-sensitive balance. The instrumentation of all groups was terminated at master apical file #25. Irrigation with 10 ml of deionized water was administered using a needle with a side vent. The collected debris weight was calculated by deducting each vial's pre-instrumentation weight from its post-instrumentation weight. The analysis of variance (ANOVA) and the honestly significant difference (HSD) tests were used to assess the statistical significance of the variation in debris levels across the groups under investigation, using a significance level of 0.05.Results: The results revealed that all tested groups had produced apical debris in different amounts.Conclusions: Under the purview of the present investigation, apical debris was produced in all tested groups. The EndoSequence CM produced less amount of debris than other tested groups. While the RM and F6 SkyTaper produced a comparable amount of apical debris. The EndoSequence ESR produced the most amount of apical debris.